Characterisation techniques for temporally structured pulses in high-repetition-rate laser-plasma wakefield accelerators - Wang, W (2024)
Multi-pulse laser-plasma wakefield accelerators (MP-LWFA) provide an alternative way towards compact and multi-kilohertz operation of GeV-scale laser-electron accelerators for advanced light sources and future particle accelerators. However, an appropriate pulse characterisation technique has not been developed for examining and optimising temporal structures of multi-pulse trains in MP-LWFA. The aim of this research is to understand whether the spectral and temporal structures of ps-long pulse trains with fine structures on the fs-scale can be characterised with a frequency-resolved optical gating (FROG) technique. A FROG device with a single-shot beam geometry was developed to measure various pulse train structures generated by the temporal interference of two chirped pulses. It was experimentally demonstrated that the single-shot FROG device, using the extended ptychographic iterative engine phase retrieval algorithm, could retrieve pulse trains with 11 pulses, a time-bandwidth-product of (16 ± 1), average pulse spacing of (232 ± 7) fs, and local pulse spacing increment of (27 ± 7) fs. The results indicate that the single-shot FROG technique could characterise pulse trains with various temporal structures. Therefore, this framework, accompanied by cross-referenced spectral interferometry, can be employed for the complete pulse characterisation of pulse trains in a novel electron acceleration scheme known as plasma-modulated plasma accelerators.